JAINFULL LEARNING MEDIA DIGITAL BERBASIS CINTA - Fauzan, Ali; Rizki, Arif; Zainuri, Ahmad; Fatimah Zahra, Frika (Jurnal Pustaka Cendekia Pendidikan, 2025)
The develolopment of digital technology has driven significant transformation in the word of education, incluiding at the madrasah ibtidaiyah (MI) level. This article aims to examine the application of adaptive learning and technology-based joyful learningin the MI environment as a strategy to answer the challenges of 21st-century learning. Using descriptive qualitative approach through a literature study, this article analyzes various literature and best practices relevant to the integration of educational technology. The results of the study indicate that adavtive learning through a digital platform allows for fersonalization of learning according to individual students needs, while joyful learning based on interactive media increases motivation, participation, and social-emotional development of student, the combination of the two creates a responsive, inclusive, and enjoyable learning environment. Technological innovations such as educational applications, Al- based learning systems, and augmented reality have proven effective in strengthening the learning engagement of MI students. This study concludes that strategic technology integration can strengthen the quality of contextual and globabally competitive Islamic basic education.